Crazy love [videorecording (DVD)] - Stevens, Fisher; Klores, Dan; Breslin, Jimmy; Pugach, Burt; Pugach, Linda (Magnolia Home Entertainment, 2007)
An examination of the human psyches of Burt and Linda Pugach. Tells the astonishing and unbelievable story of the obsessive roller-coaster relationship the couple shared. Their whirlwind romance culminated in a violent and psychologicall complex set of actions that landed the pair on the cover of endless newspapers.